Somatic features Bydgoszcz 15-year-old rowers and canoeists - Oliwia Paulina Ligman; Marek Napierała; Małgorzata Pezala; Rafał Gotowski (Kazimierz Wielki University, 2017)
The study of somatic construction was carried out in a group of 15 year old school students (53 athletes), with the help of trainers. Youth, the students and schoolgirls II middle-school classes in the secondary schools in Bydgoszcz. Measurements included: body weight and height, and the field length, width and circuits athletes. Body rowers and canoeists and rowers and canoeists at the age of 15 are close to each other, which does not mean that such differences do not exist.